If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 6 = 42 + -2x Reorder the terms: 6 + 4x = 42 + -2x Solving 6 + 4x = 42 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 6 + 4x + 2x = 42 + -2x + 2x Combine like terms: 4x + 2x = 6x 6 + 6x = 42 + -2x + 2x Combine like terms: -2x + 2x = 0 6 + 6x = 42 + 0 6 + 6x = 42 Add '-6' to each side of the equation. 6 + -6 + 6x = 42 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 42 + -6 6x = 42 + -6 Combine like terms: 42 + -6 = 36 6x = 36 Divide each side by '6'. x = 6 Simplifying x = 6
| 1-7=x-x | | .58y-.25=2y-1.7 | | -2(2x-1)+7=-4x+9 | | -8x+15=-10x+5 | | n-7=3 | | 7x-3(6-x)=16 | | 4x-1=-2x+11 | | 41=16-6-x | | n-4=20 | | 4z-1=2x+11 | | -4(x+5)-6=-26 | | (1/2)x+4=x-4 | | (12+15)(56)= | | n+20=37 | | (4-6i)(4+8i)= | | 8y+19=67 | | 41=16-x | | 4/6^2 | | x^2+72=-17x | | 16=R/2 | | x-10=abs(x^2-10x) | | -4x+6=3x-8 | | 6-2c=8-3c | | 7x-57=35 | | 5y-8=6y-4 | | T=R/2 | | 3-3(x+2)=9+x | | 7(-7)+4(x)=-28 | | y=(144)(-133) | | X^2-4y-4x=0 | | 1/4(2x+10)=3(3-3x)+3 | | 5x=24-xsquared |